The Meme and its Silences in Case of Natural Disasters: 19S in Mexico City - Albo Cos, Úrsula; Sánchez Ramírez, José Luis (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
In cases of natural disasters, societies enter into emergency and emotions overflow derived from the break with their daily lives because of the tragedy that this events generate. The aforementioned is reflected in digital social networks, where ethical codes and self-regulation of the population are made explicit about what can be said or shown and what cannot, generating moments of multiple silences and imposed for some formats, especially those which are humorous, as is the meme.